2023
DOI: 10.1021/acs.jmedchem.3c00671
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Development of Selective BRD7 Bromodomain Inhibitors and Their Activity in Prostate Cancer

Sandra C. Ordonez-Rubiano,
Chad A. Maschinot,
Sijie Wang
et al.

Abstract: Bromodomain-containing proteins are readers of acetylated lysine and play important roles in cancer. Bromodomain-containing protein 7 (BRD7) is implicated in multiple malignancies; however, there are no selective chemical probes to study its function in disease. Using crystal structures of BRD7 and BRD9 bromodomains (BDs) bound to BRD9-selective ligands, we identified a binding pocket exclusive to BRD7. We synthesized a series of ligands designed to occupy this binding region and identified two inhibitors with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Next, the effect of BD98 on rIEG transcription was assessed along with PBAF- and GBAF-specific inhibitors (2-77 61 and I-BRD9 62 , respectively). Pre-treatment with BD98, but not PBAF or GBAF inhibitors, significantly attenuated activity-induced transcription of Arc and other rIEGs (Figure 2F and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the effect of BD98 on rIEG transcription was assessed along with PBAF- and GBAF-specific inhibitors (2-77 61 and I-BRD9 62 , respectively). Pre-treatment with BD98, but not PBAF or GBAF inhibitors, significantly attenuated activity-induced transcription of Arc and other rIEGs (Figure 2F and S1A).…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrate that, in many cases, the PROTACs areadvantageous compared to the single-bromodomain ligands [169,172]. Despite the powerful effects of inhibiting bromodomain subunits, one study indicated that a disruption of SWI/SNF remodeling activity has a more profound effect on gene expression than the disruption of SWI/SNF sub-complexes through bromodomain inhibition and degradation [195]. However, the loss of ATPase subunits does not necessarily eliminate all SWI/SNF functions, as seen in cancers such as small cell carcinoma of the ovary-hypercalcemic type (SCCOHT)-where there is a dual loss of SMARCA4/2, but which retain residual complexes without the catalytic activity that may contribute to oncogenic gene expression [196].…”
Section: Discussionmentioning
confidence: 99%
“…The first BRD7-selective inhibitors were recently developed and characterized [195]. The compounds 1-78 and 2-77 showed significantly increased affinity to the BRD7 bromodomain over that of BRD9 and were unable to displace BRD9 from chromatin, even at high concentrations.…”
Section: Targeting Swi/snf Family VIII Bromodomainsmentioning
confidence: 99%